2002
DOI: 10.1038/nature01004
|View full text |Cite
|
Sign up to set email alerts
|

T-cell engagement of dendritic cells rapidly rearranges MHC class II transport

Abstract: Assembly of major histocompatibility complex (MHC) molecules, which present antigen in the form of short peptides to T lymphocytes, occurs in the endoplasmic reticulum; once assembled, these molecules travel from the endoplasmic reticulum to their final destination. MHC class II molecules follow a route that takes them by means of the endocytic pathway, where they acquire peptide, to the cell surface. The transport of MHC class II molecules in 'professional' antigen-presenting cells (APCs) is subject to tight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
383
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(404 citation statements)
references
References 21 publications
20
383
0
1
Order By: Relevance
“…6A and data not shown), suggesting that the polarization of B cell Agprocessing compartments may facilitate directional trafficking of loaded peptide-MHC complexes to the B cell surface facing the T cells, enhancing Ag presentation. Such directional trafficking has been reported recently in dendritic cells (54,55), and raises the intriguing possibility that PI3K signaling may be required for targeted release of peptide-MHC II complexes generated via BCRmediated uptake.…”
Section: Discussionsupporting
confidence: 61%
“…6A and data not shown), suggesting that the polarization of B cell Agprocessing compartments may facilitate directional trafficking of loaded peptide-MHC complexes to the B cell surface facing the T cells, enhancing Ag presentation. Such directional trafficking has been reported recently in dendritic cells (54,55), and raises the intriguing possibility that PI3K signaling may be required for targeted release of peptide-MHC II complexes generated via BCRmediated uptake.…”
Section: Discussionsupporting
confidence: 61%
“…In this case, a pathway should exist for pMHCII to travel back from ILVs to the endosomal-delimiting membrane from where it could then reach the plasma membrane. Such a pathway, also referred to as "back-fusion" or retrofusion of ILVs, was also proposed to explain the disappearance of the MVB during DC maturation (Kleijmeer et al 2001) and to provide a source of membrane needed for the formation of MIIC-associated tubules in maturing DCs (Boes et al 2002(Boes et al , 2003Chow et al 2002;Vyas et al 2007). More recently, however, it was shown that such membrane tubules can be generated as a consequence of homotypic endosome fusion (Skjeldal et al 2012), which is accelerated in maturing DCs (van Nispen tot Pannerden et al 2010).…”
Section: Mvb Dynamics and Mhcii Peptide Loadingmentioning
confidence: 99%
“…Maintenance of MHCII ubiquitination in endocytic compartments other than phagosomes within the same cell would enhance selectivity in MHCII presentation of pathogen-derived peptides. Transfer of pMHCII from pathogen-loaded phagosomes to the plasma membrane can occur unidirectionally, for example, toward immunological synapse between DC and T cells (Boes et al 2002;Keller et al 2007), applying yet another layer of specificity.…”
Section: Autonomous Phagosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Des mécanismes antérogrades doivent aussi être pris en compte. Ainsi, lors des interactions T-DC, des réponses calciques [18] et des polarisations dynamiques d'actine dans les DC [49] ont été observées, suivies de l'envoi, par les DC, de chapelets de vésicules chargées en CMH de classe II [50]. Les DC reçoi-vent donc, des lymphocytes T, des signaux précoces qui peuvent influencer la formation de la synapse T-DC.…”
Section: Modifications Des Synapses Induites Par Leur Fonctionnementunclassified